Implementasi Pembelajaran IBSC (Investigation Based Science Collaborative) untuk Meningkatkan Literasi Sains Siswa - Nafiah, Qurrotul Ayunin; Puspitarini, Sapti (Paedagogie, 2026)
Science literacy in Indonesia is still low based on PISA results, so learning innovations such as the IBSC model of collaborative inquiry are needed to train students' scientific thinking, communication, and collaboration skills. This study aims to analyze the effect of implementing the ecosystem-based Investigation Based Science Collaborative (IBSC) learning model on improving junior high school students' science literacy in food chain and food web material. This study used a quantitative approach with a pre-experimental one-group pretest-posttest design, conducted at SMP Negeri 32 Surabaya in class VII-C with 30 students as samples. The instruments included an observation sheet on the implementation of learning, a science literacy test (pretest-posttest), and a student response questionnaire. Data analysis used the Shapiro-Wilk normality test, Wilcoxon test, N-gain, and descriptive analysis. The results showed that the implementation of IBSC learning was very good, with a percentage of 95.63% in the first meeting and 97.22% in the second meeting. Students' science literacy increased significantly (sig. <0.001), with an average N-gain score of 0.72 (high category), where 68% of students reached the high category and 32% reached the medium category. Improvements were seen in the indicators of explaining scientific phenomena (N-gain 0.69), developing investigation plans (N-gain 0.83), and interpreting data/evidence (N-gain 0.73). Students' responses to active and collaborative learning were highly positive (>85%). In conclusion, the ecosystem-based IBSC model effectively improves students' science literacy through an investigative and collaborative approach, which is applied to the development of meaningful and contextual science learning. This study recommends the sustainability of the IBSC model with a focus on data analysis and expansion of research subjects.